Idiopathic intracranial hypertension presenting as acute bilateral loss of vision (Indian Journal of Case Reports, 2021)
cute bilateral vision loss is a very rare presentation of idiopathic intracranial hypertension (IIH). We report the case of a 17-year-old female student who presented with a history of moderate degree headache from 7 days and severe loss of vision of 6 days duration. The vision loss initially affected the right eye and over the next 2 days, her left eye was also involved. Her visual acuity in both eyes was 6/60 and she had a relative afferent pupillary defect on the right side. Fundus examination showed bilateral papilledema and perimetry showed severe bilateral constriction of visual fields with the involvement of central areas as well. Cerebrospinal fluid opening pressure was raised and magnetic resonance imaging showed signs suggestive of IIH. She was managed with acetazolamide, topiramate, and lumbar drainage. She showed a gradual improvement in her vision, and finally, her visual acuity returned to normal.